Effects of long-term training cessation in young top-level road cyclists - Maldonado-Martín, S.; Cámara, J.; James, D. V.; Fernández-López, J. R.; Artetxe-Gezuraga, X. (Journal of Sports Sciences, 2014)
In cycling, it is common practice to have a break in the off season longer than 4 weeks while adopting an almost sedentary lifestyle, and such a break is considered to be long-term detraining. No previous studies have assessed the effect of training cessation with highly trained young cyclists. The purpose of the present investigation was to examine effects of 5 weeks of training cessation in 10 young (20.1 ± 1.4 years) male road cyclists for body composition, haematological and physiological parameters. After training cessation, body mass of cyclists increased (P = 0.014; ES = 0.9). (L/min = -8.8 ± 5.0%, mL/kg/min = -10.8 ± 4.2%,), Wmax (W = -6.5 ± 3.1%, W/kg = -8.5 ± 3.3%,), WLT1 (W = -12.9 ± 7.0%, W/kg = -14.8 ± 7.4%,), WLT2 (W = -11.5 ± 7.0%, W/kg = -13.4 ± 7.6%,) and haematological (red blood cells count, -6.6 ± 4.8%; haemoglobin, -5.4 ± 4.3% and haematocrit, -2.9 ± 3.0%) values decreased (P = 0.028; ES = 0.9). Five weeks of training cessation resulted in large decreases in physiological and haematological values in young top-level road cyclists suggesting the need for a shorter training stoppage. This long-term detraining is more pronounced when expressed relative to body mass emphasising the influence of such body mass on power output. A maintenance programme based on reduced training strategies should be implemented to avoid large declines in physiological values in young cyclists who aspire to become professionals.